Menakar Proyeksi Tingkat Pengangguran Terbuka di Indonesia: An Approach Quantitative Study Using Arima Model - Ambrosius Rana Putra Sar Prawintara; Asmara Sufi; Muhammad Farid Hernawan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Unemployment is a condition in which a person who is qualified and wants to work cannot find a job that matches his or her skills and desires, and is actively seeking work. In Indonesia itself, the large unemployment rate is still a macro problem faced in the national economy. This research aims to forecast the Open Unemployment Rate (TPT) in Indonesia for the next ten years from 2022 to 2032. This research uses the ARIMA model to be the basic assumption for the forecasting calculations to be carried out. The results show that the selected ARIMA model is ARIMA (2,1,0)(0,1,0)1 with data quality that has been stationary and meets diagnostic checks. The Open Unemployment Rate in Indonesia is predicted to increase every year until 2032. The need to expand investment in job openings in a number of employment units must be boosted.